Patient Identification in Wards: What Influences Nurses’ Complicance? - Tri Wahyuning Rahmawati; Dwi Ratna Sari; Devita Rahmani Ratri; Mafrurrochim Hasyim (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Patient safety is important because people have easy information and hospital reports related to medical errors. Patient identification is the most important cause of patient safety incidents. In 2019, 12 near misses due to misidentification of patients in the inpatient, laboratory, and pharmacy at the private class D hospital in Blitar. This prompted the authors to conduct a case study and analyze the causal factors of the problems. The method used in this research is descriptive and case study approach. Identification of the root problems was done by observation and interviews with implementing inpatients rooms nurses using observation sheets. Determination of the root problems is determined through a two-stage focus group discussion (FGD) using a fishbone diagram. Six root problems were found that affect the low compliance in the implementation of patient identification in inpatient installations, they are low supervision and supervision from the leadership, no resocialization regarding patient identification, a small number of patients, lack of safety culture, lack of supporting tools, and patients’ willingness to be served quickly. Knowing the root factors that affect the officers’ compliance is essential so supervision methods that are appropriate to the conditions of the hospital can be conducted.